2007
DOI: 10.14411/fp.2007.037
|View full text |Cite
|
Sign up to set email alerts
|

Four new myxozoans (Myxosporea: Bivalvulida) from intertidal fishes along the south coast of Africa

Abstract: Abstract. Current records of marine myxozoans from the coast of Africa are limited to the descriptions of 52 species from mostly Senegal, with a few from Tunisia and southern Africa. Between 1998 and 2000 several intertidal fishes from the southern Cape coast of South Africa were examined for the presence of myxozoan infections. Three new species, Ceratomyxa dehoopi sp. n., C. cottoidii sp. n. and C. honckenii sp. n. were identified from the gall bladders of Clinus superciliosus L., C. cottoides Valenciennes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…However, attachment of C. puntazzi to the gall bladder epithelium was not observed in the present study, although widely reported in other Ceratomyxa spp. [42][44]. The type of cytokinesis observed for the Myxozoa in the present study does not match all characteristics of the existing models type B or C and it is still unclear if it can be ascribed to one of them, however, it is clear that it excludes the formation of a myosin II-dependent contractile ring (Cytokinesis type A).…”
Section: Discussioncontrasting
confidence: 90%
“…However, attachment of C. puntazzi to the gall bladder epithelium was not observed in the present study, although widely reported in other Ceratomyxa spp. [42][44]. The type of cytokinesis observed for the Myxozoa in the present study does not match all characteristics of the existing models type B or C and it is still unclear if it can be ascribed to one of them, however, it is clear that it excludes the formation of a myosin II-dependent contractile ring (Cytokinesis type A).…”
Section: Discussioncontrasting
confidence: 90%
“…During the period 1918 to 1930 he reported various types of myxosporeans from gall bladders of several South African fishes, mainly intertidal (Fantham 1918a(Fantham , 1918b(Fantham , 1919(Fantham , 1930. None of his descriptions contained sufficient descriptive information and illustrations, making it impossible to distinguish them from other similar species and, according to Reed et al (2007), are considered to be nomina nuda. However, his work was not in vain as it drew the attention of researchers to the possibility of myxozoans inhabiting the gall and urinary bladders of South African intertidal fish and indirectly led to the description of Ortholinea basma Ali, 2000 from the urinary bladder of the agile klipfish, Clinus agilis; subsequently, the descriptions of three more myxozoans followed, namely Ceratomyxa dehoopi Reed, The most infamous of all myxosporeans from South Africa was described in 1924 by the ichthyologist John Dow Fisher Gilchrist from the muscles of the Cape sea fish, or 'snoek', Thyrsites atun.…”
Section: Myxozoamentioning
confidence: 99%
“…Most of the Henneguya spp. have been recorded from the gills, skin, and kidneys of freshwater fish (Eiras 2002 (Kpatcha et al 1997;Eiras 2002;Yokoyama et al 2003Yokoyama et al , 2005Reed et al 2007;Work et al 2008). In addition, H. ogawai sp.…”
Section: Remarksmentioning
confidence: 99%